Marava sp. (DERMAPTERA: LABIIDAE), PREDADOR DO ÃCARO HEMATÃ“FAGO EM AVIÃRIOS - Costa, Valmir Antonio; Berti Filho, Evoneo; Makhoul, Maria Flávia (REVISTA DE AGRICULTURA, 2015)
Marava sp. (DERMAPTERA: LABIIDAE), PREDADOR DO ÃCARO HEMATÃ“FAGO EM AVIÃRIOS